Amyloidosis: A story of how inframammary erosions eclipsed inconspicuous periorbital ecchymoses - Andrew Kelsey, MD; Diane H. Smith, MD; Joyce Meng, MD; Michael Murphy, MD; Marti J. Rothe, MD (Wolters Kluwer, 2016)
Systemic amyloidosis is a rare disease that can be rapidly progressive due to widespread organ involvement. There are well-described renal, cardiac, pulmonary, neurological, and dermatologic findings. Here, we outline one patient's experience with the condition from presentation to making the diagnosis. She presented with pathognomonic dermatologic findings including pinch purpura and ecchymoses found in the skin folds. Key words: apple-green birefringence, amyloid, amyloidosis, Congo red, inframammary erosions, periorbital ecchymoses, pinch purpura, plasma-cell dyscrasia, serum protein electrophoresis